Research on the Algorithm about Optical Fiber Parameters Measurement - Chen Xiao-rong; Cong Yuan; Xi Chuan-li (Institute of Advanced Engineering and Science, 2013)
We can measure the geometry parameters of the optical fiber efficiently and intelligently for the use of machine vision technology, the main operations contain threshold segmentation, removing interference, filtering, fitting etc. Compared with the traditional optical fiber measurement algorithm, this method has the advantages of high processing speed, high accuracy and not too relying on the operation level. It can also be applied to the size measurement of other small linear object. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3517